Redesigning Professional Education Doctorates Applications of Critical Friendship Theory to the EdD - Storey, Valerie A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This volume demonstrates that Critical Friendship Theory can help distinguish education doctorate (EdD) programs from research doctorates (education PhDs). Drawing on multiple, detailed case studies of CFT implementation at universities, it covers curriculum and implementation, online and in-person education, challenges, and strategies for success.
Keywords: Education; Curriculums (Courses of study).; Education -- Curricula; School management and organization; School administration; Higher education; Education -- Philosophy; Social sciences; Education; Administration, Organization and Leadership; Higher Education; Social Sciences, general; Curriculum Studies; Educational Philosophy; Professional & Vocational Education